A humanized microbiota mouse model of ovalbumin-induced lung inflammation. (3rd July 2016) - Arrieta, Marie-Claire; Sadarangani, Manish; Brown, Eric M.; Russell, Shannon L.; Nimmo, Michael; Dean, John; Turvey, Stuart E.; Chan, Edmond S.; Finlay, B. Brett
ABSTRACT: There is increasing evidence for a role of early life gut microbiota in later development of asthma in children. In our recent study, children with reduced abundance of the bacterial genera Lachnospira, Veillonella, Faecalibacterium, and Rothia had an increased risk of development of asthma and addition of these bacteria in a humanized mouse model reduced airway inflammation. In this Addendum, we provide additional data on the use of a humanized gut microbiota mouse model to study the development of asthma in children, highlighting the differences in immune development between germ-free mice colonized with human microbes compared to those colonized with mouse gut microbiota. We also demonstrate that there is no association between the composition of the gut microbiota in older children and the diagnosis of asthma, further suggesting the importance of the gut microbiota-immune system axis in the first 3 months of life.